Pengaruh Good Corporate Governance, Leverage dan Sales Growth terhadap Kinerja Keuangan pada Perusahaan Sektor Consumer Non Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Eka, Annisa Eka Safitri; Mulyani, Sri; Afifi, Zaenal (Jurnal Akuntansi Publik Nusantara, 2025)
This study aims to examine the effect of good corporate governance, leverage, and sales growth on financial performance. This study uses secondary data sources in the form of financial reports of Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the years 2019-2023. Using a purposive sampling method, a sample of 145 companies was obtained. Data analysis used multiple linear regression analysis. Based on the results of hypothesis testing, it was found that institutional ownership has a positive effect on financial performance, the audit committee has no effect on financial performance, leverage has a negative effect on financial performance, and sales growth has a positive effect on financial performance.